Proyecto socioeducativo para la prevención del maltrato infantil, con padres, madres y educadoras del centro infantil Gotitas de Amor Barrio Pilacoto - Vargas Valiente, Fanny Clemencia (2017)
The purpose of this paper is to show the process carried out in the educational project for the prevention of child abuse, in the CIBV "droplets of Love" in the Pilacoto district belonging to the parish Guaytacama Canton Latacunga. The prevention of abuse against Children project was carried out, seeking to obtain results that would allow the reduction of abuse in the children of the Barrio Pilacoto. In work a diagnostic phase was applied on the perception of abuse and a sensitization phase carried out through the workshop modality. The diagnosis and its results, it is described as a problem and antecedent, then the scope and limits of the proposal enunciate the topics worked, in the process of sensitization. For the implementation of this process, a referential framework was developed which supports the proposal, which addressed the concept of abuse, types of abuse and the consequences, and an approximation on the educational intervention, complemented by the development of the child. The first workshop was carried out to diagnose the situations of abuse in the Children's center. A sensitization workshop was then carried out with the intention of preventing child abuse, for this process a methodological proposal was applied which was based on the experiential model of learning; for this last workshop, several topics related to child abuse were raise